Preliminary studies on the morphology of natural rubber-polypropylene blends using scanning electron microscopy - Che Husna Azhari; Zamri Yusoff; Jaafar Sahari (1992)
The morphology of natural rubber/polypropylene (NR/PP) blends were studied using scanning electron microscopy (SEM). The NR/PP blends were produced in varying compositions of NR/PP ratios of 80:20, 70:30, 60:40, 50:50, 40:60 and 30:70. The NR/PP blends were sputter coated with gold and observed under a Phillips 500 SEM at magnifications of 0.326K and 2.5K respectively. Micrographs showed the blends as incompatible polymers with NR domains embedded in a continous PP matrix. At higher NR loadings, the NR domains were observed to be fibrils interspersed continously in the PP matrix whilst at lower loadings the NR phase was scattered in distinct granular domains. Models of the NR/PP blends were postulated frorn the micrographs obtained